The Effect of Soaking Time of Melinjo (Gnetum Gnemon L.) Peel Powder on Peroxide Numbers in Bulk Cooking Oil - Fardani, Roushandy Asri; Purwita, Ni Wayan Mustika (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Bulk oil is cooking oil that has gone through refining, bleaching, and deodorizing stages. Bulk cooking oil has been distributed in unpackaged form, which means that bulk cooking oil is exposed to oxygen before use. Incorrect storage over a period of time can cause the rupture of triglyceride bonds in the oil which eventually forms glycerol and free fatty acids (Yola, 2018). Bulk cooking oil that reacts with oxygen will cause the peroxide number to increase. High peroxide numbers are very dangerous for health. The content of saponins, tannins and flavonoids found in melinjo peel can be an antioxidant that acts as an antidote to free radicals so that it can slow down oxidation in bulk cooking oil. The purpose of this study was to determine the effectiveness of melinjo peel powder as an antioxidant with variations in soaking time on peroxide numbers in bulk cooking oil. This type of research is experimental with the number of repetitions of samples 16 From the results of the examination, the average peroxide number in bulk cooking oil that has been soaked is 0 day 22.7949 mEq, 4 days 19.5965 mEq and 8 days 9.5984 mEq. Statistical analysis using Kruskal-Wallis test obtained Sig value. 0.003 <0.05 indicates the effect of soaking time of melinjo peel powder on peroxide number in bulk cooking oil.